2014
DOI: 10.1007/978-3-642-44955-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Strong Boards, Risk Committee and Bank Performance: Evidence from India and China

Abstract: The recent financial crisis has raised several questions with respect to the corporate governance of financial institutions. This paper investigates whether boards of directors and risk management-related corporate governance mechanisms are associated with a better bank performance during the financial crisis of 2007/2008 for a sample of Chinese and Indian listed banks. We measure market bank performance by Tobin’ Q and price-earnings ratio. In line with the previous literature on US banks, we find the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…The coefficient that is associated with natural logarithm of total assets (LNTA) indicates that, if the size increases by 1%, we foresee an increase in liquidity risk by 0.005401. This supports our first hypothesis and is also consistent with the aforementioned theoretical background of larger banks being riskier (Battaglia et al 2014;De Haan and Poghosyan 2012). Moreover, the probability of moral hazard will rise if larger banks increase their lending activity at a lower franchise, whereas holding adequate levels of capital contributes not only to a decrease in liquidity risk but also to a reduction in the incidence of eventual losses.…”
Section: Preliminary Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The coefficient that is associated with natural logarithm of total assets (LNTA) indicates that, if the size increases by 1%, we foresee an increase in liquidity risk by 0.005401. This supports our first hypothesis and is also consistent with the aforementioned theoretical background of larger banks being riskier (Battaglia et al 2014;De Haan and Poghosyan 2012). Moreover, the probability of moral hazard will rise if larger banks increase their lending activity at a lower franchise, whereas holding adequate levels of capital contributes not only to a decrease in liquidity risk but also to a reduction in the incidence of eventual losses.…”
Section: Preliminary Resultssupporting
confidence: 89%
“…It has been found that bigger banks are not riskier (Birindelli et al 2018;Bertay et al 2013;Mercieca et al 2007;Demsetz and Strahan 1997). On the other hand, studies have shown that larger banks are less stable (Battaglia et al 2014;De Haan and Poghosyan 2012). We expect a positive sign for the banking size coefficient, which means that larger banks tend to increase their liquidity risk, thus we posit: Hypothesis 1.…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…Moreover, the complex nature of risk management, and the skills required to manage risks, does not necessarily match with the skills of AC members. Battaglia et al (2014) and Zaman (2001) assert that because of their lack of expertise and time, ACs do not offer a solution to risk management that is robust enough, considering the fact that ACs are already over-burdened because of additional responsibilities of abiding by the code of CG and regulatory reforms. Based on these lessons, recommendations put forward by Walker (2009), at the request of the Prime Minister of the UK, emphasize the establishment of a board level separate risk committee (RC) in banks and other financial institutions with the responsibility to oversee current and future risks.…”
Section: Cfpmentioning
confidence: 99%
“…Thus, many FIs establish independent risk committees to cover responsibilities such as, suggest risk appetite and risk limits, limit breaks and mitigation procedures, review risk profile and risk monitoring, receive and review risk issues reports, stress test scenarios, and review, update and accept risk policies change (Battaglia et al, 2014;BCBS, 2015;Elamer et al, 2017;Ng et al, 2012). Therefore, RC as internal corporate governance structure can improve and assist the board of directors in managing risks in FIs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many FIs establish independent risk committees to cover responsibilities such as, suggest risk appetite and risk limits, limit breaks and mitigation procedures, review risk profile and risk monitoring, receive and review risk issues reports, stress test scenarios, and review, update and accept risk policies change (Battaglia et al, 2014;BCBS, 2015;Elamer et al, 2017;Ng et al, 2012). Therefore, RC as internal corporate governance structure can improve and assist the board of directors in managing risks in FIs.…”
Section: Introductionmentioning
confidence: 99%